Regulatory roles of Bxy-laf-1 in reproductive behaviour of Bursaphelenchus xylophilus - Sun, Shimiao; Wang, Jinghan; Liu, Wenyi; Chen, Jing; Zhou, Lifeng; Wu, Choufei; Yu, Hongshi; Hu, Jiafu (Frontiers in Physiology, 2022)
Bursaphelenchus xylophilu is a worldwide quarantine nematode, causing huge economic losses and ecological disasters in many countries. The sex ratio of B. xylophilus plays an important role in the nematode infestation. The laf-1-related genes are highly conserved in animals, playing crucial roles in sex determination. Therefore, we investigated the expression pattern and biological function of its orthologue, Bxy-laf-1 in B. xylophilus. Bxy-laf-1 has two typical conserved DNA-binding domains, DEAD and Helicase C. The real-time quantitative PCR data revealed that Bxy-laf-1 expression was required throughout the entire life of B. xylophilus, with the maximum expression in the J2 stage and the lowest expression in the adult stage. mRNA in situ hybridization showed that Bxy-laf-1 is mainly located in the cephalopharynx and reproductive organs of B. xylophilus. RNA interference (RNAi) indicated that head swing frequency was dramatically decreased. The RNAi results displayed that a significant reduction in motility was observed in the hatched larvae. The female and male sex ratio was also decreased in the F0 and F1 generations, but recovered in the F2 generation. The tail of female adults with eggs in the belly appeared deformities. This phenomenon appeared in the F0 and F1 generations, but recovered in the F2 generation. Bxy-laf-1 is a typical sex-determination gene with distinct expression patterns in males and females. As demonstrated in other species, the sex ratio was altered after knocking down Bxy-laf-1 expression. The results of this study contribute to our understanding of the molecular processes of Bxy-laf-1 in B. xylophilus, which may provide clues about how to control pine wilt disease by inhibiting ontogenic growth and reducing nematode fertility.